Mutually testing processes - HENNESSY, MATTHEW (My University, 2015)
This volume contains the proceedings of the 24th Conference on Concurrency Theory (CONCUR 2013) held in Buenos Aires, Argentina, during August 27–30, 2013. CONCUR 2013 was organized by the Universidad de Buenos Aires and the Universidad Nacional de C ́ ordoba. The purpose of the CONCUR conference is to bring together researchers, developers, and students in order to advance the theory of concurrency and pro- mote its applications. The principal topics include basic models of concurrency such as abstract machines, domain theoretic models, game theoretic models, process algebras, and Petri nets; logics for concurrency such as modal logics, probabilistic and stochastic logics, temporal logics, and resource logics; models of specialized systems such as biology-inspired systems, circuits, hybrid systems, mobile and collaborative systems, multi-core processors, probabilistic systems, real-time systems, service-oriented computing, and synchronous systems; ver- ification and analysis techniques for concurrent systems such as abstract in- terpretation, atomicity checking, model checking, race detection, pre-order and equivalence checking, run-time verification, state-space exploration, static anal- ysis, synthesis, testing, theorem proving, and type systems; related programming models such as distributed, component-based , object-oriented, and Web services. This edition of the conference attracted 115 submissions. We would like to thank all their authors for their interest in CONCUR 2013. After careful review- ing and discussions, the Program Committee selected 34 papers for presentation at the conference. Each submission was r eviewed by at least three reviewers, who wrote detailed evaluations and gave insightful comments. The Conference Chairs would like to thank the Program Committee members and all the additional re- viewers for their excellent work, as wel l as for the constructive discussions. We are grateful to the authors for having revised their papers so as to address the comments and suggestions by the referees. The conference program was greatly enriched by the invited talks by Lorenzo Alvisi (joint invited speaker with QEST 2013), Joost-Pieter Katoen, Philippe Schnoebelen, and Reinhard Wilhelm (joint invited speaker with FORMATS 2013).
Keywords: CONCUR 2013; CONCUR 2013